ANALISIS BIBLIOMETRIK DAN VISUALISASI STRATEGI KOMUNIKASI POLITIK PEREMPUAN PADA DATA SCOPUS TAHUN 2010 HINGGA 2023 - Osha Elitya Oktaviani; Karim Suryadi; Sri Wahyuni Tanshzil (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
The development of politics in Indonesia, which increasingly involves the role of women in the political system, is progressing. The purpose of this study is to conduct a bibliometric analysis of articles on women's political communication strategies sourced from the Scopus database from 2010 to 2023. This journal employs bibliometric analysis using the Vosviewer application. The Vosviewer analysis revealed 18 articles on women's political communication strategies. These articles were then classified based on publication year, authors, affiliations, keywords, and journal titles. The authors also conducted a literature review on articles about women's political communication strategies from the Scopus database. This research provides valuable insights into the characteristics and content of articles on political communication strategies. However, to thoroughly understand the content and findings of each article and to develop new knowledge in this field, further research is needed.